Structural Behavior of Prestressed Concrete Bridge Girder with Monolithic Joint - Jalairov, Assylkhan; Kumar, Dauren; Kassymkanova, Khaini-Kamal; Nuruldaeva, Gulzhan; Imankulova, Arailym (Communications - Scientific Letters of the University of Zilina, 2022)
The paper presents the results of a test on a composite bridge girder of a length of 42.0 m, which was performed to assess its resistance, stiffness and crack resistance. Composite reinforced concrete beam with three blocks is joined by the two monolithic joints. When testing a beam with monolithic joint in terms of stiffness, crack resistance and strength, a load of 943.5 kN was achieved without cracking, which is 26.8 % higher than the required one.
Keywords: composite bridge prestressed concrete beam; monolithic joint; beam strength; beam stiffness; beam crack resistance